2021
DOI: 10.1080/17512786.2020.1870531
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Delivery Mistakes, Gender, and Empathic Concern on Source and Message Credibility

Abstract: This study explores the impact of television news anchor delivery mistakes on message and source credibility evaluations and whether gender, news context, and empathic concern moderate this effect. The results of an experiment showed that viewers have the highest appraisal of anchors with perfect delivery, and evaluation suffers precipitously with increased mistakes. When evaluating short news clips, viewers were more tolerant of the female news anchor making three delivery mistakes than the male, but both gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In another experiment using writings by journalists as inductions, male journalists were found to be more credible than female journalists when making the same claims (Klaas & Boukes, 2020). Yet, other studies have found that females were perceived to be more credible when evaluated for identical delivery mistakes in news broadcasting contexts (Gong & Eppler, 2022). In another experiment of source credibility using transcriptions of crime reports, men judged female-authored transcripts to be more credible while women perceived no difference in credibility of transcripts based on author gender (Rozmann & Levy, 2021).…”
Section: Credibilitymentioning
confidence: 88%
“…In another experiment using writings by journalists as inductions, male journalists were found to be more credible than female journalists when making the same claims (Klaas & Boukes, 2020). Yet, other studies have found that females were perceived to be more credible when evaluated for identical delivery mistakes in news broadcasting contexts (Gong & Eppler, 2022). In another experiment of source credibility using transcriptions of crime reports, men judged female-authored transcripts to be more credible while women perceived no difference in credibility of transcripts based on author gender (Rozmann & Levy, 2021).…”
Section: Credibilitymentioning
confidence: 88%